Covid-19 Related Factors Associated with Antenatal Care in Rural Bangladesh: A qualitative study - S. M. Mostafa Kamal; Dr. M Anisur Rahman; Dr. Sonia Singh (ACHSM, 2022)
Objective: Available literature reveals that usage of Maternal Health Care Services (MHCSs), including antenatal care (ANC), has been decreased significantly in the developing countries due to Corona Virus Disease (COVID-19) pandemic. However, the COVID-19 related factors on the MHCSs utilization in Bangladeshi women are yet to be examined. Therefore, this study examines the effect of COVID-19 on the use of ANC services among rural communities in Bangladesh. Method: A community-based qualitative study was conducted from May 01, 2021, to July 20, 2021, among selected pregnant women residing in eight villages of the Kushtia District, Bangladesh. A total of ten focus group discussions (FGDs) was conducted. Open Code 4.0 software was used to transcribe, translate, and analyze the data thematically. Results: Findings suggest that the measures taken by the government against the COVID-19 pandemic have significantly decreased the optimum usage of ANC services. The need to shift the role of the health workforces a vital factor that has a negative effect on women's attitude towards seeking MHCSs. Anxiety, dirty and poor environment of the health facilities, low quality of care, stigma, and risk minimization strategy are among other factors that refrained the pregnant women from seeking ANC services. Conclusion: Undoubtedly, the COVID-19 related factors have decreased the possible usage of ANC services among rural communities in Bangladesh. Additional necessary health workforces are needed to recruit urgently. A special wing for pregnant women in each health facility may be opened as a one-stop service center for the COVID-19 period. The policymakers should take necessary actions to reduce anxiety among pregnant women and motivate them to use MHCSs for safe motherhood.